The educational conception in the training of female nurses and male nurses reproduces the hegemonic educational scheme of the formation of human resources in health - Jácome, Goretti (2018)
The objetive of the presente study was to establish the more frequent practices of the educative process in the nursing career of the Universidad Central del Ecuador, in the period from July to December 2015. A descriptive  study was carried out with the participation of 156 students, chosen on a non-random basis, belonging to all  the semesters of the nursing career, to whom a questionnaire was applied. With the same students, focus groups were organized, divided by semester, and the topics of the survey questions were discussed. The most noteworthy results of the survey were: 85% accepted that the class reflects on the diversity of the Ecuadorian reality in terms of ethnicity, gender and generations. The 90% agreed that the theoretical contents are approached reflexively. In 80% of classes the monologue dominates. In the educational process the teacher imposes and generates dependency in 85%. These results opposed opinions of group meetings. The reproduction of knowledge in a unidirectional way remains the norm of teaching in the nursing career